2004
DOI: 10.4067/s0717-75262004000600006
|View full text |Cite
|
Sign up to set email alerts
|

Biotipos y susceptibilidad antimicrobiana de Gardnerella vaginalis

Abstract: Se determinaron los biotipos y susceptibilidad a ampicilina, clindamicina, eritromicina, ciprofloxacina y tetraciclina de 63 cepas de Gardnerella vaginalis aisladas de pacientes con vaginosis bacteriana. Las cepas se distribuyeron en los 8 biotipos del esquema de clasificación de Piot, siendo los biotipos 1 y 2 los más frecuentes (44,4%). Todas las cepas fueron susceptibles a ampicilina y resistentes a ciprofloxacina. Cuatro cepas (6,4%) presentaron resistencia a clindamicina y dos (3,2%) a eritromicina. Trein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…OR-dependent and neural activity-dependent pathways in glomerular segregation converge in the expression pattern of axon sorting molecule. To date, several studies identified multiple activity-dependent axon-sorting molecules that are expressed in OSNs (St John et al, 2002;Cutforth et al, 2003;Kaneko-Goto et al, 2008;Williams et al, 2011;Ihara et al, 2016;Mountoufaris et al, 2017;Vaddadi et al, 2019;Wang et al, 2021;Martinez et al, 2023). The exact number of molecules implicated in this process is still unclear, but a handful of transmembrane proteins are thought to be involved.…”
Section: Molecular Mechanisms Of Or-dependent Glomerular Map Refinementmentioning
confidence: 99%
“…OR-dependent and neural activity-dependent pathways in glomerular segregation converge in the expression pattern of axon sorting molecule. To date, several studies identified multiple activity-dependent axon-sorting molecules that are expressed in OSNs (St John et al, 2002;Cutforth et al, 2003;Kaneko-Goto et al, 2008;Williams et al, 2011;Ihara et al, 2016;Mountoufaris et al, 2017;Vaddadi et al, 2019;Wang et al, 2021;Martinez et al, 2023). The exact number of molecules implicated in this process is still unclear, but a handful of transmembrane proteins are thought to be involved.…”
Section: Molecular Mechanisms Of Or-dependent Glomerular Map Refinementmentioning
confidence: 99%
“…Os catalisadores heterogêneos podem minimizar os impactos ambientais gerados pela eliminação de rejeitos químicos quando se utiliza o ácido sulfúrico como catalisador, atendendo aos princípios da Química Verde. [20][21][22][23][24][25]…”
Section: Dean-starkunclassified